2006
DOI: 10.1159/000092796
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Stroke and Stroke-Associated Mortality in Patients with a Hospital Diagnosis of Nonvalvular Atrial Fibrillation or Flutter

Abstract: Aim: There are few data on seasonal variation in stroke and seasonal variation in mortality after stroke in patients with atrial fibrillation. We examined the seasonal pattern in stroke occurrence and the effect of the season on mortality after stroke in patients with a history of nonvalvular atrial fibrillation. Methods:We identified all individuals, aged 40–89 years, with an incident diagnosis of stroke of any nature (ischemic or hemorrhagic) in the 1980–2002 period and no history of heart valve disease and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 44 publications
3
8
1
4
Order By: Relevance
“…About a half of the studies have demonstrated a majority of new cases of stroke during the winter season [27,28], about 40% of the studies -during summer [29,30], while 10-12% of the trials have revealed no significant seasonality [31], so as our research has.…”
Section: Winter Cardiovascular Morbidity In Ivanovo Region сердечно-сmentioning
confidence: 58%
“…About a half of the studies have demonstrated a majority of new cases of stroke during the winter season [27,28], about 40% of the studies -during summer [29,30], while 10-12% of the trials have revealed no significant seasonality [31], so as our research has.…”
Section: Winter Cardiovascular Morbidity In Ivanovo Region сердечно-сmentioning
confidence: 58%
“…66 However, other studies have failed to produce consistent support for this hypothesis. [67][68][69][70] Moreover, it is unlikely that season could have confounded the data presented here, because both advertising campaigns covered more than one season (late autumn, winter, spring, and early summer for the first campaign, and winter, spring, and most of the summer for the second campaign).…”
Section: Discussionmentioning
confidence: 95%
“…Сезонные изменения в природе являются неотъемлемой частью среды обитания, и присущие им флуктуации факторов внешней среды приобретают условно-рефлек-торное значение [5]. В ряде исследований отме-чено, что в осенне-зимний период увеличивается заболеваемость острым нарушением мозгового кровообращения (ОНМК) [18,20,21]. Некото-рые авторы указывают на рост числа случаев ОНМК в весенне-летний период [16,17].…”
unclassified